Analisis salasilah Tarekat Shaykh Shams al-Din al-Sumatra’i - Rohaimi Rastam; Mohd Syukri Yeoh Abdullah; Yusri Mohamad Ramli (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
This article examines the spiritual chain (silsilah tariqah) of Shaykh Shams al-Din al-Sumatra’i (alt. al-Sumatrani), Qadi al-Malik al-‘Adil (Prime Minister and Mufti) of Aceh during the reign of Sultan Iskandar Muda in 1607 to 1627. The study is primarily based on his manuscript of Mir’at al-Muhaqqiqin as well as Shaykh Abdul Haqq Muhaddith Dahlawi’s Zad al-Muttaqin. By mapping the lineage of all data available, this study features al-Sumatra’is spiritual chain that consist of Qadiriyyah, Shadhiliyyah, Madyaniyyah, Chishtiyyah and Shattariyyah orders.